P-176 SHIP1 Deficiency in Human IBD: Molecular Basis, Prognosis and Agonist Development. (March 2016) - Kerr, William; Fernandes, Sandra; Middleton, Frank; Chisholm, John; Ryan, James
Abstract : Background: The causes of IBD are not fully known. Significant insights into the etiology of human IBD have come from Genome-Wide Association Studies (GWAS), which have identified more than 100 different inherited mutations that influence the risk of IBD in affected families. Only about 10% to 15% of all IBD adult patients have any of these genetic mutations. This means that risk factors for approximately 85% of IBD patients have yet to be defined. We have previously shown that mutation of SHIP1 leads to a Crohn's-like ileitis in mice. We hypothesized that loss of SHIP1 might potentially contribute to IBD in humans. Methods: SHIP1 expression was analyzed by qRT-PCR, Western blot, intracellular flow cytometry (icFlow) and RNAseq in-patient PBL. Results: In order to determine if SHIP1/INPP5D deficiency might also contribute to human IBD, we analyzed SHIP1 expression in more than 100 adult IBD patients. We find that ∼15% of the adult IBD population demonstrates a profound degree of SHIP1 deficiency at the protein level (<10% of normal). However, both qRT-PCR and RNAseq analysis indicate these SHIP1-deficient patients have normal SHIP1 mRNA expression. Exome sequencing of the entire SHIP1/INPP5D gene in 8 separate SHIP1-deficient patients revealed no coding changes in the SHIP1/INPP5D gene that could account for the profound decrease in SHIP1 protein expression. Treatment of blood leukocytes with a proteasome inhibitor significantly increases SHIP1 protein expression in SHIP1 deficient patient PBL, but has the opposite effect in SHIP1-sufficient patients PBL. Flow cytometric analysis showed that SHIP1-deficient patients have a significant reduction in circulating CD4 + T cells, as do CD4CreSHIPflox/flox mice that have a selective ablation of SHIP1 expression in T lineage cells. In order to identify mutations or changes in gene expression at other loci that could adversely impact SHIP1 protein expression we performed RNAseq analysis on 10 separate SHIP1 deficient patients. Comparison of their transcriptomes to normal healthy controls indicates profound disruption of gene expression in SHIP1 deficient IBD patients. We also recently assessed disease severity in SHIP1 deficient IBD patients. We find that 63% of SHIP1-deficient CD patients have had surgical resection of their GI tract versus 23% in the SHIP1-sufficient cohort ( P = 0.024) and have required on average 1.9 resections versus 0.3 in the SHIP1-sufficient CD cohort ( P = 0.009). We also performed a computational drug screen that led to the identification of a novel SHIP1 agonist, K204. Using a human T cell model of SHIP1 protein deficiency, we show that K204 can significantly increase SHIP1 protein expression in intact cells. Conclusions: We find that a significant proportion of IBD patients have a profound reduction of SHIP1 expression. SHIP1 deficiency appears to have an adverse impact on disease progression as more than 60% of CD patients that are SHIP1-deficient require surgical resection of their GI tract, including multiple resections. We also find that SHIP1 protein is preferentially degraded by the proteasome system in SHIP1-deficient patients. Importantly, proteasome inhibitors and a novel SHIP1 agonist can partially restore SHIP1 protein expression suggesting a novel therapeutic approach in IBD.